Place of Occurrence of Injury Events in New Zealand Compared with the Available ICD Codes - Langley, John D.; Chalmers, David J. (Methods of Information in Medicine, 1989)
The distribution of the place of occurrence of selected injury events in New Zealand was compared with the allocation of place of occurrence codes in the International Classification of Disease (ICD). National injury mortality and morbidity data for 1984 were upgraded to provide more specific information on the location of injury events than is allowed by the ICD codes. This highlighted a number of shortcomings in the ICD codes. For example, whereas only 0.1% of the injury morbidity occurred in a mine or quarry, 57 times that amount occurred on a rugby league ground. Despite this, mines and quarries have a unique code and rugby grounds are included under the general code “place for recreation and sport”. Several modifications to existing codes are proposed. The lack of mutually exclusive categories, the confusion of activity with place of occurrence, and restrictions in the recommended use of the codes are discussed.
Keywords: ICD; Injury; Place of Occurrence